Effect of Semen Collection in the Metabolite and Hormonal Content of Rabbit Seminal Plasma - Manuel Álvarez‐Rodríguez; Laura García‐Calvo; Jaume Gardela; Mateo Ruiz‐Conca; Sergi Olvera‐Maneu; Adrián Martín‐San Juan; Manel López‐Béjar; Felipe Martinez‐Pastor; Alejandro Vicente‐Carrillo (Veterinary Medicine and Science)
ABSTRACT Blood serum (BS) and seminal plasma (SP) share a plethora of compounds that might present an individual and/or temporal concentration variation. We aimed to determine whether BS and SP concentrations of albumin, calcium, citrate, creatinine, fructose, glucose, lactate, total protein, urea, zinc, cortisol, anti‐Müllerian hormone (AMH) and testosterone are related to weekly collections in New Zealand White (NZW) adult rabbit bucks. During a 12‐week study, blood samples were obtained at the beginning and the end of the study period, and semen samples were taken twice a week from four NZW adult rabbit bucks, starting at 6–7 months of age. After semen collection, the sperm motility was subjectively assessed, and SP was obtained by centrifugation. BS and SP were evaluated for the above‐mentioned metabolites using a Biosystems BA400 automated analyser with commercial‐specific kits or enzyme immunoassay (EIA) kits, assessing the effects of the male and time of collection. In addition, a correlation analysis aimed at disclosing associations between parameters in BS and SP was performed. Male effect was not significant for BS, but it was significant for SP albumin, citrate, fructose, glucose, lactate and total protein. In addition, all the correlations in BS were positive, whereas they were more balanced in SP, being close to half of the correlations. In conclusion, variations of some metabolites (albumin, citrate, fructose, glucose, lactate and total protein) appear to be potential biomarkers for rabbit SP, although further studies should test their usefulness for sperm fertility assessment.